Merumuskan Formula Pakan Ayam Kampung Petelur Menggunakan Model Interval Linier Programing - Diki Muchtar Diki (Jurnal Rekayasa Teknologi dan Sains Terapan, 2022)
ABSTRACTThere have been several researchs conducted on the feed formulation such as (Samuel Olugbenga .O et al, 2015) linier programing, (F.Zhang W.B.Roush, 2002) mutiple-objective programming, (Brigitta Ayu Kusuma Wardhany et al, 2017) Particle swarm optimization, (Nur Firra Hasjidla et al, 2018) Improved Particle swarm optimization, (I.U. Udo et al, 2011) linier programming, (Thuleswar Nath, 2014) linier programing without interval coefficient. This research is like a Thuleswar Nath research but uses interval data (interval coefficient) so that it requires a interval linear programming model in feed formulation that is the best and the worst case method (M.allohdadi,2012). This research aims to determine parameters and variables of model for feed formulations with a interval linear programming model and calculate the optimum solution to decide the total cost required according to the nutrients needed. The data is processed using the best and the worst case method (interval linear programming) than after that it is optimized using linear programming software. Optimum solution of the worst case is 587.958.1, with the consentrate (x1) 43,52 kg, Corn (x2) 42,41 kg, Rice Bran (x3) 0 kg, Tofu Dregs (x4) 6,43 kg , Cassava Dregs (x5) 7,62 kg. And than optimum solution of the best case is 425.686.6, with the consentrate (x1) 29,62 kg, Corn (x2) 51,02 kg, Rice Bran (x3) 2,51 kg, Tofu Dregs (x4) 6,20 kg , Cassava Dregs (x5) 10,63 kg.